2022
DOI: 10.3390/jof8080825
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Species of Talaromyces Discovered in a Karst Cave in the Satun UNESCO Global Geopark of Southern Thailand

Abstract: Karst caves are oligotrophic environments that appear to support a high diversity of fungi. Studies of fungi in Thailand’s caves are limited. During a 2019 exploration of the mycobiota associated with soil samples from a karst cave, namely, Phu Pha Phet in the Satun UNESCO Global Geopark in Satun Province, southern Thailand, two previously undescribed fungi belonging to Talaromyces (Trichocomaceae, Eurotiales, Eurotiomycetes) were studied using a polyphasic approach combining phenotypic and molecular data. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Talaromyces mellisjaponici has been isolated from honey, despite previous studies suggesting that species in section Trachyspermi are mainly found in soil and living or decayed plants [7–11]. Only six Talaromyces species have been reported in honey, including T. scorteus from section Islandici , T. brasiliensis , T. affinitatimellis and T. basipetosporus from section Trachyspermi , T. brunneosporus from section Purpurei , and T. funiculosus from section Talaromyces [14, 15, 34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Talaromyces mellisjaponici has been isolated from honey, despite previous studies suggesting that species in section Trachyspermi are mainly found in soil and living or decayed plants [7–11]. Only six Talaromyces species have been reported in honey, including T. scorteus from section Islandici , T. brasiliensis , T. affinitatimellis and T. basipetosporus from section Trachyspermi , T. brunneosporus from section Purpurei , and T. funiculosus from section Talaromyces [14, 15, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis was done, encompassing the entire section Trachyspermi , utilizing combined ITS, BenA , CaM and RPB2 sequences. Published sequence data from Rodríguez-Andrade et al [15, 21], Nuankaew et al [11], Houbraken et al [22] and Zang et al [23] were included (). The sequences were aligned using mafft version 7 [24], and the resulting alignment was submitted to TreeBASE (ID 30596).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, under field conditions, the Talaromyces flavus isolate Tfl (anamorph Penicillium dangeardii , also known as P. vermiculatum ) suppresses verticillium wilt of eggplant (Brunner et al, 2005) and has the ability to suppress the verticillium wilt of potato [ 108 ]. In the soil, Talaromyces is a strong competitor [ 109 ].…”
Section: Mechanisms Of Fungal Endophytesmentioning
confidence: 99%
“…Nuankaew et al 18 recently discovered two new Talaromyces species in soil samples from the Satun UNESCO Global Geopark in Thailand, a region with scarce documentation of fungi in tropical caves. As part of a mycological diversity study in the Satun UNESCO Global Geopark, this research aimed to explore the fungi present in two karst caves, Phu Pha Phet Cave and Le Stegodon Cave.…”
Section: Introductionmentioning
confidence: 99%